2017
DOI: 10.1016/j.actbio.2016.12.054
|View full text |Cite
|
Sign up to set email alerts
|

The pressure-induced deformation response of the human lamina cribrosa: Analysis of regional variations

Abstract: The objective of this study was to measure the pressure-induced deformation response of the human lamina cribrosa (LC) and analyze for variations with age and anatomical region. The posterior scleral cup of 8 eyes from 6 human donors was mounted onto a custom inflation chamber. A laser-scanning microscope was used for second harmonic generation (SHG), imaging the collagen structure in the posterior volume of the LC at pressures from 5 mmHg to 45 mmHg. The SHG volumes were analyzed by the Fast-Fourier Iterative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
87
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 66 publications
11
87
2
Order By: Relevance
“…Accurate characterization of the effects of IOP on the neural tissues of the LC is critical to understanding the pathogenesis and progression of glaucoma as the LC neural tissues are hypothesized to be damaged by IOP-induced mechanical insult. Our conclusions are largely in agreement with recent experimental testing which has predicted similar behavior [1820]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Accurate characterization of the effects of IOP on the neural tissues of the LC is critical to understanding the pathogenesis and progression of glaucoma as the LC neural tissues are hypothesized to be damaged by IOP-induced mechanical insult. Our conclusions are largely in agreement with recent experimental testing which has predicted similar behavior [1820]. …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our data suggested that the amount of stretch or compression varied largely from one pore to another. Peak strains exceeding 10% have been reported by Midgett and colleagues who also used second harmonic generation to measure the deformation of human LCs [20]. While both of these studies were done ex vivo, we have also recently measured strains in vivo in the LC of rhesus macaque monkeys under various levels of IOP and intracranial pressure using optical coherence tomography [19].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Normal lamina cribrosa structure is remodeled in glaucoma eyes, becoming deeper and wider 8 under the influence of a variety of factors, notably the stress of IOP as delivered through the sclera. 9 The regional differences in connective tissue density and pore size within the lamina cribrosa and greater regional strains suggest that the upper and lower poles of the ONH are weaker at resisting the stress of IOP in both human [10][11][12][13][14] and nonhuman primate eyes. 15 Indeed, these regions contain the axons of the RGCs most susceptible to glaucoma injury.…”
mentioning
confidence: 99%
“…These incongruities could arise due to alteration in stiffness of the ocular tissues and their response to elevated IOP. These factors are material determinants of IOP-derived lamina strain which is related to glaucoma occurrence [6]. Elevated IOP induces distention of the sclera and lamina cribrosa and impose direct mechanical strain on the axons of the optic nerve damaging nerve fibers and potentially impairing the nerve’s blood supply.…”
Section: Introductionmentioning
confidence: 99%